2016
DOI: 10.1111/jftr.12167
|View full text |Cite
|
Sign up to set email alerts
|

How to Define Situated and Ever‐Transforming Family Configurations? A New Materialist Approach

Abstract: In recent decades, the concept of family has been subjected to redefinition as family scholars have debated the question of who and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 46 publications
2
24
0
6
Order By: Relevance
“…By considering the multiple entanglements of people, all the activities they are part of, and all the participants that are temporarily linked to them, new materialist-inspired socialization research can advance the understanding of socialization processes, how they in fact develop and become durable. New materialist theories base themselves on non-reductionism and take into account the complex relations of everyday life, e.g., the connection between technologies and family structures (Schadler, 2016). Further processes that can become visible through the lens of new materialism could enrich the research field of socialization and aging, for instance by studying the relationships between spaces, architectures, commodity items, and "becoming old. "…”
Section: Contribution Of New Materialist Ideas To Socialization Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…By considering the multiple entanglements of people, all the activities they are part of, and all the participants that are temporarily linked to them, new materialist-inspired socialization research can advance the understanding of socialization processes, how they in fact develop and become durable. New materialist theories base themselves on non-reductionism and take into account the complex relations of everyday life, e.g., the connection between technologies and family structures (Schadler, 2016). Further processes that can become visible through the lens of new materialism could enrich the research field of socialization and aging, for instance by studying the relationships between spaces, architectures, commodity items, and "becoming old. "…”
Section: Contribution Of New Materialist Ideas To Socialization Researchmentioning
confidence: 99%
“…The following example clarifies this argument. Schadler (2013Schadler ( , 2016 has impressively shown that socialization research distinguishes between "a presocial biological body and an immaterial social personality, " and thus "between a biological and a social birth" (Schadler, 2016: p. 506). In her research on the formation of the nuclear family during the transition to parenthood, she demonstrates that socialization processes in families are instead both cultural procedures that start even before the physical pregnancy and material processes that include human bodies and include things and technologies during the whole transition process (Schadler, 2013).…”
Section: Dualismsmentioning
confidence: 99%
See 3 more Smart Citations